Liquid AbobotulinumtoxinA: Pooled Data From Two Double-Blind, Randomized, Placebo-Controlled Phase III Studies of Glabellar Line Treatment. Issue 11 (7th November 2022) - Hilton, Said; Kestemont, Philippe; Sattler, Gerhard; Volteau, Magali; Thompson, Catherine; Andriopoulos, Bill; Prygova, Inna; Berg, Anna-Karin; Ascher, Benjamin
Abstract : Supplemental Digital Content is Available in the Text. Abstract : BACKGROUND: AbobotulinumtoxinA (aboBoNT-A) solution is a new ready-to-use formulation developed to reduce preparation time and improve reproducibility of injections. OBJECTIVE: To further evaluate treatment of moderate-to-severe glabellar lines (GLs) using pooled data from 2 Phase III studies. METHODS: Following double-blind treatment with 50 U aboBoNT-A solution (n = 251) or placebo (n = 123), GL severity was assessed by investigators (ILA) and subjects (SSA). Other assessments included subject-reported time to onset, subject satisfaction, FACE-Q, and adverse events. RESULTS: One month after aboBoNT-A solution treatment, 88% had none-or-mild GLs at maximum frown and 93% had ≥1-grade improvement in ILA (similar for SSA), 24% to 27% remaining improved at Month 6. Glabellar lines responder rates remained higher than placebo throughout Month 6 ( p < .001). Almost two-thirds of subjects reported onset within 3 days, nearly a quarter reporting effect by Day 1. Subject satisfaction with GL appearance, and FACE-Q satisfaction with facial appearance overall and psychological well-being were also improved over placebo throughout Month 6, p < .05. Treatment-related adverse events were nonserious and mild or moderate. CONCLUSION: Pooled analysis confirmed a duration of effect on GLs of up to 6 months for aboBoNT-A solution, with onset starting within 24 hours, high subject satisfaction, and improved psychological well-being. The treatment was well tolerated.